Kenaikan Ekspor dan Impor Tahun 2022 Terhadap Pendapatan Nasional Indonesia - Rima Pratiwi, Rosiati; Ramadhanti, Dita; Sholihah, Afifah; Kustiawati, Dedek (Rifa'Institute, 2023)
International trade is crucial for countries to fulfill their needs and boost their economies. The COVID-19 pandemic has affected domestic and international trade. Indonesia's economy remains relatively strong, with growth projections above global projections. National income is an important indicator for measuring a country's economic growth. There are three approaches to calculating national income: production, income, and expenditure. This study focuses on the expenditure approach. The purpose of this study is to examine the impact of the increase in exports and imports from October 2021-2022 on Indonesia's national income. The research was conducted by collecting and analyzing data from the Indonesian Central Bureau of Statistics (CBS), as well as utilizing library research methods. The findings suggest that changes in the value of exports and imports will affect national income, making them significant factors that impact a country's national income.